The Readiness Level of Special Education Teachers in Learning Strategies of Students with Hearing Disability - Nor Fatihah Suhada Mohamed Ali; Suziyani Mohamed (Department of Special Education, 2017)
This study aims to identify special education teachers’ readiness in teaching strategies used during the teaching and learning of students with hearing disability. There were three constructs examined in this study which are teachers’ knowledge on hearing disability, teachers’ knowledge on the use of hearing aids and teachers’ mastery in the use of sign language. Teachers’ knowledge and mastery on these three constructs are very crucial to ensure the teaching and learning process are carried out effectively. Quantitative approach was employed to collect the data in this study, and a survey research design and questionnaires were used to collect data. The questionnaires consist of three parts, (a) demographic information, (b) knowledge level, and (c) skill level. The data were analysed with SPSS and descriptive analysis was utilized. The findings showed that the overall mean of teachers’ knowledge on hearing disability is high whereas the overall mean on teachers’ skills are of medium level. Teachers need to understand the needs of students in order for teaching strategies to be effective. Teachers’ level of readiness depends on the knowledge and skills of teachers to manage the teaching process of students with hearing disabilities.